PREISWERKITE AND NA-(MG,FE)-MARGARITE IN ECLOGITES - Godard G.; Smith D. (My University, 1999)
Preiswerkite and Na-(Mg,Fe)-margarite are two unusual micas very rare in Nature. They have been observed together in two eclogite occurrences (La Compointrie, France; Liset, Norway) as retrogression products in coronae or symplectites around kyanite. The chemical compositions and some physical properties of these micas are presented. The possible solid solutions and the conditions of stability are discussed. The preiswerkites display slight solid solution towards phengitic muscovite and Na-phlogopite. On the other hand, there is negligible solid solution towards more aluminous compositions; AlIV ≤ 4 appears to be a composition limit for natural (K,Na)-micas. The margarites have an unusual Na-(Mg,Fe)-rich composition. They can be considered as a solid solution of about 2/3 mol% of margarite and 1/3 mol% of the theoretical end-member Na2(Mg,Fe)1AlVI4[Si4AlIV4]O20(OH)4 (“Mica L”), with a possible substitution towards paragonite. The Marg2/3 Mica L1/3 composition (i.e. NaCa2(Mg,Fe)0.5 AlVI6 [Si6AlIV6]O30(OH)6) might represent a particularly stable crystallographic configuration and could be considered as a true end-member. Many “sodian” margarites described in the literature are, in fact, complex solid solutions between margarite, paragonite and Marg2/3 Mica L1/3. The rarity of these micas is not related to extreme or unusual P-T conditions. They seem to be related to unusual chemical compositions, appearing in H2O-saturated Na-Al-rich Si-poor systems, principally, if not only, at greenschist- or amphibolite-facies P-T conditions. Moreover, they are subject to crystallographic constraints whereby the high proportion of Al-tetrahedra create considerable distortion which prevents the entry of K into the interlayer site, thus necessitating Na (preiswerkite or ephesite) or Ca (margarite or clintonite) instead.